(untitled) (Journal of Bio-Science, 2018)
The demand of environmentally friendly packaging materials to overcome the high use of plastic led to increase of research effort on the development of biodegradable plastic from sustainable packaging. In this research, carrageenan films containing of arrowroot starch in the polymer blend were obtained using polyethylene glycol as plasticizer. The objective is to study the effect of different concentrations of arrowroot starch (20%, 40%, 60%, 80% of carrageenan based) on barrier property (water vapor transmission rate), mechanical properties (thickness, tensile strength and elongation at break), solubility in water and whiteness index of the obtained biofilm samples. The result shows that all of them have good transparency, with 60% of concentration gives the highest Whiteness Index. The concentration of arrowroot starch that shows the best resistance to tensile strength is 40%, as well as in thickness values. Concentration of 80% shows the lowest water vapor transmission rate (WVTR) permeability with 85.12 g/m2.24h, while the lowest water solubility is obtained from 60% concentration with 60.49% solubility. The recommended level of arrowroot starch to be incorporated in the process of arrowroot starch-carrageenan-based film is 60% of carrageenan. J. bio-sci. 25: 45-56, 2017